Stability analysis in variable structure position/force hybrid control of manipulators - Azenha, Abílio (1997)
In this paper it is studied the implementation of a variable structure algorithm in position/force hybrid control of robotic manipulators. The robustness and performances of the system are analysed both in terms of time and frequency responses.